原発性副甲状腺機能亢進症に生じた下顎骨褐色腫の1例 - 町田, 好聡; 渋谷, 亜佑美; 肥後, 智樹; 越沼, 伸也; 山本, 学; 齋藤, 翔太 (日本口腔外科学会雑誌, 2015)
A brown tumor is a giant cell bone lesion that occurs as a complication of hyperparathyroidism. We report a case of mandibular brown tumor associated with primary hyperparathyroidism in a 27-year-old man. Computed tomography (CT) showed a large bilateral tumor in the mandibular region, and biopsy of the mandibular tumor showed a giant cell lesion. The laboratory data showed hypercalcemia and hyperparathyroidism. Contrast-enhanced CT revealed a cystic lesion on the right parathyroid gland. On the basis of these findings, the mandibular tumor was diagnosed to be a brown tumor. Three years 5 months have passed since right parathyroidectomy was performed, and the mandibular bone brown tumors have disappeared bilaterally. Moreover, the progress of the patient has been good.